Effect of Interleukin-17 in the Activation of Monocyte Subsets in Patients with ST-Segment Elevation Myocardial Infarction - Montserrat Guadalupe Garza-Reyes; Mónica Daniela Mora-Ruíz; Luis Chávez-Sánchez; Alejandra Madrid-Miller; Alberto Jose Cabrera-Quintero; José Luis Maravillas-Montero; Alejandro Zentella-Dehesa; Luis Moreno-Ruíz; Selene Pastor-Salgado; Erick Ramírez-Arias; Nataly Pérez-Velázquez; Adriana Karina Chávez-Rueda; et al. (Journal of Immunology Research)
Interleukin- (IL-) 17 is increased in acute myocardial infarction (AMI) and plays a key role in inflammatory diseases through its involvement in the activation of leukocytes. Here, we describe for the first time the effect of IL-17 in the migration and activation of monocyte subsets in patients during ST-segment elevation myocardial infarction (STEMI) and post-STEMI. We analyzed the circulating levels of IL-17 in patient plasma. A gradual increase in IL-17 was found in STEMI and post-STEMI patients. Additionally, IL-17 had a powerful effect on the recruitment of CD14++CD16+/CD14+CD16++ monocytes derived from patients post-STEMI compared with the monocytes from patients with STEMI, suggesting that IL-17 recruits monocytes with inflammatory activity post-STEMI. Furthermore, IL-17 increased the expression of TLR4 on CD14+CD16- and CD14++CD16+/CD14+CD16++ monocytes post-STEMI and might enhance the response to danger-associated molecular patterns post-STEMI. Moreover, IL-17 induced secretion of IL-6 from CD14++CD16− and CD14++CD16+/CD14+CD16++ monocytes both in STEMI and in post-STEMI, which indicates that IL-17 has an effect on the secretion of proinflammatory cytokines from monocytes during STEMI and post-STEMI. Overall, we demonstrate that in STEMI and post-STEMI, IL-17 is increased and induces the migration and activation of monocyte subsets, possibly contributing to the inflammatory response through TLR4 and IL-6 secretion.